Guardians of the Karri Forests - Hungerford, T. A. G. (Indian Forester, 1953)
In the South-western corner of Australia there are va.st tracts of forest which contain millions of super feet of karns, one of the best hardwoods known - an asset of inestimable value in a world of shrinking timber resources. The most modern and comprehensive precautions are taken to ensure a sustained yield and protect them from the most savage enemy, the forest fire.